Ground Vibration Analysis of Railroad Dynamic Loads on Rail Structure - Kusumawardani, Rini; Zelin, Mufita Aulia; Kusbiantoro, Arief (Jurnal Teknik Sipil dan Perencanaan, 2019)
The railroad structure consists of rail steel, sleepers, fastening, ballast, sub-ballast and subgrade. The load of the passing train at a certain speed can produce vibrations channeled through the train wheels to the railway steel to be forwarded to the sleepers then to the ballast and distributed to the subgrade. The amount of vibration caused by the train can be seen from the value of the acceleration, amplitude and frequency of the vibration. In this study, the accelerometer sensor was used to detect the magnitude of the vibration acceleration. The vibration acceleration data was then processed using Geopsy software to obtain the value of natural frequency and vibration amplitude using the HVSR (Horizontal to Vertical Spectral Ratio) method. The value of acceleration due to railroad vibration of 0.14 g - 0.64 g with a position placed 1.5 m sensor from the edge of the rail. The biggest vibration acceleration is 0.26 g x direction, 0.39 y direction and 0.29 z direction caused by Maharani trains that pass at a speed of 65 km / h and a load of 728 tons. The natural frequency of vibration obtained value 2.4077 Hz - 5.392 Hz. The highest natural frequency was caused when the Maharani train, which was 5.392 Hz. Train speed and load affected the vibration of the rail structure. The acceleration of vibration increased when the train speed and load increased